A method for preparing a simulated sample of a fractured formation rock and a simulated sample of a fractured formation rock

CN115184102BActive Publication Date: 2026-10-20CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110354392.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-01
Publication Date
2026-10-20
Estimated Expiration
2041-04-01

AI Technical Summary

Technical Problem

显然,该方法也受限于裂缝数量的限制,而且操作起来非常复杂

Benefits of technology

[0028]本发明采用天然露头作为模拟试样的基质,相对于现有技术中用水泥浇筑形成基质,其中的水泥只是一种类岩石材料,其结构与力学性能与真实岩石有很大差距,难以准确反映真实岩石材料的力学属性和裂隙扩展机理。而天然露头是真实岩石,其作为模拟真实岩石的基质更具有结构和力学的代表性、针对性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115184102B_ABST
    Figure CN115184102B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a broken formation rock simulation sample and the rock simulation sample, and the preparation method comprises the following steps: collecting crack information of a formation rock to be simulated, determining a broken mode and a quantitative crack distribution feature; determining standard sizes and quantities of the simulation rock sample according to the broken mode of the formation rock to be simulated, the crack distribution feature and the size of the simulation sample; stacking the simulation rock sample in a simulation sample mold according to the broken mode, and placing water-soluble paper between contact surfaces of the simulation rock sample; the thickness of the water-soluble paper is equivalent to the crack width; pouring and forming the simulation rock sample arranged in the simulation sample mold by using a rock-like material, and curing and demolding to obtain the broken formation rock simulation sample. The method has strong applicability and operability, can realize accurate control of the crack number density, shape and cementing strength of the broken formation rock sample, and provides a basic guarantee for carrying out large-scale borehole wall stability physical simulation experiments of the broken formation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rock simulation technology, and more specifically, to a method for preparing a rock simulation sample of fractured strata and a rock simulation sample, particularly a method for preparing a rock simulation sample specifically for fractured strata and capable of considering the fracture morphology, fracture density and fracture cementation strength of fractured cemented strata. Background Technology

[0002] Fractured formations refer to rock masses exhibiting fractured mechanical behavior and physical mechanisms under external forces, encompassing various weak surface structures such as faults, cleavage, and fractures. The most common fractured formations are low-strength brittle rocks such as coal seams, shale layers, limestone, and certain types of dolomite. When drilling into these formations, wellbore collapse is often severe, not only wasting significant drilling time and materials and causing a rapid increase in drilling costs, but also affecting the quality of subsequent operations.

[0003] In the field of petroleum engineering, wellbore instability is frequent during drilling in fractured formations, severely hindering the acceleration and efficiency of drilling and completion. The presence of fracture surfaces in fractured rock masses disrupts their integrity. For formations with well-developed fractures, faults, and weak surfaces, coring is difficult and costly; unlike shale and sandstone outcrops, it is difficult to cut complete simulated samples from fractured rock masses using natural outcrops. Therefore, artificially preparing large-scale simulated rock samples is the only way.

[0004] In the existing technology, the preparation methods for simulated rock samples of fractured or cracked strata can be divided into three categories: (1) placing natural rock fragments in a mold and then injecting rock-like materials (cement mortar or low-strength concrete) into the mold to form the sample. For example, patent CN105352786A discloses a method for preparing and loading fractured rock samples, which is suitable for preparing specimens of weak and fractured rock blocks. Specifically, it includes removing dust from the surface of easily fractured rock blocks and applying pressure adhesive; placing the adhesive-injected rock blocks in a hollow cuboid or cubic box and pouring cement mortar or low-strength concrete to form the sample; placing the rock blocks formed by mortar or low-strength concrete on a corer for core extraction; and then cutting the sample to obtain the required standard rock sample. And patent CN102866050A "A Method for Preparing Specimens of Irregular and Easily Fragile Coal and Rock Blocks" discloses a method for preparing rock mechanics specimens applicable to irregular and easily fragmented coal and rock bodies. The method involves coating the surface of easily fragmented or irregularly shaped coal and rock blocks with waterproof material, placing them in a mold suitable for the size of the coal and rock blocks, uniformly brushing a layer of release agent that does not react with cement on the inner surface of the mold, injecting the prepared cement slurry into the mold, making the mold densely filled, and after reaching the design strength, drilling cylindrical specimens with a core drill, and then cutting off the cement slurry solidified sections at both ends of the drilled cylindrical specimens with a rock cutter, leaving only the coal and rock block section, and then grinding it to obtain the required coal and rock specimen. Although this method is simple, it cannot achieve controllable crack characteristics such as crack density, distribution pattern and cementation strength; (2) By selecting complete rock samples, the complete rock samples are cut with the help of electric wire saws and moving components. This method can control the crack angle characteristics, but it can only be used to make finite fracture rock samples. The number of cracks in finite fracture rock samples is generally less than 5-6. Once the number of cracks increases, it is difficult to effectively cut and make cracks. At the same time, this method can only be used to make continuous cracks. (3) By using the strip extraction method, mica sheets, kraft paper, thin steel sheets and aluminum sheets are pre-embedded in the model to make discontinuous non-continuous unfilled cracks, and then cast into shape using rock-like materials. This method can be used to make finite fracture rock samples and can also control the morphological characteristics of cracks to a certain extent. However, once the number of cracks increases, crack control will be very difficult, and the pre-made crack materials will differ greatly from the real cracks, resulting in poor representativeness.

[0005] Furthermore, patent CN106092699A, "Apparatus and Method for Creating Three-Dimensional Discontinuous Through-Fire Fractures in a Cuboid Rock Sample," discloses an apparatus comprising a frame, an electric wire saw assembly mounted on the frame, a three-dimensional movement assembly, a sample fixing assembly, and a fracture width control assembly. Employing the three-dimensional movement and sample fixing assemblies, it enables multi-directional three-dimensional adjustment of a real rock sample, meeting the requirements for creating through-fiber fractures. The method involves determining the position and size of multiple discontinuous pre-fabricated fractures within the cuboid rock sample, and drilling holes at both ends of each pre-fabricated fracture, thus creating through-holes penetrating the top and bottom surfaces of the rock sample corresponding to the ends of the pre-fabricated fractures. However, this method involves drilling holes at both ends of each pre-fabricated fracture in a single cuboid rock sample to obtain through-fiber fractures. Clearly, this method is also limited by the number of fractures and is very complex to operate.

[0006] In the field of petroleum engineering, fracture structures in fractured rock samples are complex, and there are currently no suitable simulation methods or simulation samples for fractures in fractured rock samples. Summary of the Invention

[0007] To address the problems in existing technologies, this invention proposes a method for preparing simulated rock samples specifically for fractured strata, as well as the simulated rock samples themselves. This invention uses natural outcrops to represent the matrix of fractured strata, processes them into simulated rock samples of different sizes, and then constructs simulated rock samples using water-soluble paper, a special stacking method between simulated rock samples, and casting with rock-like materials. This allows for precise control over the distribution density, morphology, and cementation strength of fractures in fractured strata.

[0008] One objective of this invention is to provide a method for preparing simulated rock samples from fractured strata, the method comprising the following steps:

[0009] (1) Collect fracture information of the rocks in the strata to be simulated, determine the fracture mode, and quantify the fracture distribution characteristics;

[0010] The rock formation to be simulated is a fractured rock formation;

[0011] (2) Based on the fracture mode, crack distribution characteristics and size of the simulated rock sample, the standard size and quantity of the simulated rock sample are determined by geometric similarity criteria.

[0012] The simulated rock sample is a cube prepared from the natural outcrop corresponding to the rock formation to be simulated. Specifically, the natural outcrop can be cut into standard sizes. An outcrop is the portion of an underground rock mass, stratum, or mineral deposit that is exposed on the surface. Those that are exposed on the surface due to geological processes (such as crustal movement, wind and water erosion) are called natural outcrops.

[0013] (3) The simulated rock samples are stacked in the simulated sample mold according to the fracture mode. Water-soluble paper is placed between the contact surfaces of the simulated rock samples. By placing water-soluble paper between the contact surfaces of the simulated samples, it is ensured that the standard rock blocks are in point contact through the water-soluble paper to simulate cracks. The thickness of the water-soluble paper is equivalent to the crack width.

[0014] (4) The simulated rock sample placed in the simulated sample mold is cast and molded using a rock-like material. After curing at room temperature indoors, the simulated rock sample of the fractured strata is obtained by demolding.

[0015] The water-soluble paper is made of polyvinyl alcohol or sodium carboxymethyl cellulose, which are commonly used water-soluble paper components in existing technologies. It can dissolve in water and completely dissolves during the casting process without leaving redundant cracks or affecting the bonding between simulated rock samples.

[0016] Preferably, in step (1), the fracture information of the rock formation to be simulated is obtained by formation imaging logging, downhole rock fragmentation, downhole core and CT scanning, which can directly reveal the morphological characteristics of the fracture and other parameters, and then directly simulate the rock fracture morphology in the simulation sample.

[0017] Preferably, in step (1), the quantitative crack distribution characteristics include the distribution pattern, width, number density and bonding strength of the quantitative cracks; the distribution pattern of the cracks includes parameters such as the angle between the cracks and the horizontal ground and the type of cracks.

[0018] Preferably, the breaking mode includes a simple layered horizontal seam pattern, a pattern with a set of strong seams and a set of weak seams at an angle, or a completely breaking orthogonal breaking seam pattern.

[0019] Preferably, in step (3), before placing the simulated rock sample in the simulated sample mold, the surface of the simulated rock sample is de-dusted. The purpose of de-dusting is simply to improve the bonding performance between the crack filling material and the rock block during the later pouring of the crack.

[0020] Preferably, in step (3), there are at least five water-soluble paper contact points between the contact surfaces of the simulated rock sample; and the water-soluble paper contact points are distributed at least at the four vertices of the contact surface of the simulated rock sample and at the center point of the contact surface.

[0021] Preferably, in step (4), the rock-like material is prepared by mixing water, cement, and gypsum in a certain proportion. The shear strength of the rock-like material corresponds to the cementation strength of the crack, and is used to simulate different crack strengths. After the rock-like material is solidified into a sample, the shear strength of the solidified rock-like material is equal to the cementation strength of the crack. The shear strength of the rock-like material can be verified by the following two methods in the prior art: one is to make a standard 5cm cubic sample of the rock-like material and perform a direct shear test; the other is to make a standard small rock sample of the rock-like material and perform a uniaxial / triaxial test, and evaluate it by the internal friction angle and cohesion.

[0022] Preferably, in step (4) of the present invention, the mass ratio of water, cement and gypsum in the rock-like material is 0.5-1:1.5-3:1-4, which corresponds to a shear strength of 2-5 MPa after the rock-like material body is consolidated.

[0023] The curing days after the simulated rock sample is poured in this invention include, but are not limited to, 18-23 days, with the specific number of days depending on the weather and the degree of maturation of the rock-like material.

[0024] Preferably, the size of the simulated sample includes, but is not limited to, 300*300*300mm, 400*400*400mm or 1000*1000*1000mm. This size is set according to the size of the simulated sample that the true triaxial equipment used can accommodate; in the embodiment, 400*400*400mm is used as an example.

[0025] Preferably, nine water-soluble paper contact points are set between the contact surfaces of the simulated rock sample, and the water-soluble paper contact points are also distributed on four equally divided points on the diagonal of the contact surface of the simulated rock sample near the vertex of the contact surface of the simulated rock sample.

[0026] A second objective of this invention is to provide a simulated rock sample of fractured strata prepared by the method described in one objective of this invention.

[0027] Beneficial effects:

[0028] This invention uses natural outcrops as the matrix for simulating samples. In contrast, existing technologies use cement to form the matrix, where cement is merely a rock-like material with significantly different structures and mechanical properties from real rock, making it difficult to accurately reflect the mechanical properties and crack propagation mechanisms of real rock. Natural outcrops, being real rock, are more representative and specific in terms of structure and mechanics when used as a matrix to simulate real rock.

[0029] This invention uses a rock-like material to simulate the cementation strength of rock cracks. Compared with cementing materials such as resin, the rock-like material is closer to the composition and structural properties of rocks and is more representative. Furthermore, the proportion of the rock-like material can be varied according to the different cementation strengths of different cracks. The strength of the rock-like material is controllable, and it can simulate cracks with different degrees of cementation, making it more convenient to use.

[0030] The invention uses a small amount of water-soluble paper, which effectively controls the crack width and reduces the interference of the water-soluble paper on the simulation effect. When the rock-like material in this invention is poured, because the water-soluble paper does not completely occupy the gaps between the simulated rock samples, the rock-like material can penetrate the gaps more completely to create cracks with cementation strength; the better the filling and the better the cementation, the better the simulation effect.

[0031] This invention uses natural outcrops to represent the matrix of fractured strata and processes them into simulated rock samples of different sizes. Then, using water-soluble paper, it simulates the special stacking method between rock samples and uses rock-like materials to construct simulated rock specimens, so as to achieve precise control over the distribution density, morphology and cementation strength of fractures in fractured strata.

[0032] This invention prepares large-scale physical simulation samples of wellbore stability and uses true triaxial equipment to conduct analysis on the deformation law, instability characteristics and mechanism of wellbore in fractured formations, which can provide theoretical guidance for proposing targeted technical control strategies.

[0033] In the field of petroleum engineering, fractured rock samples may have cemented through-cracks or cemented non-through-crack structures, resulting in complex fracture structures. This invention is specifically designed for fracture simulation methods and the preparation of simulated samples for fractured rock samples. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of a simple layered horizontal stitch mesh pattern of the present invention;

[0035] Figure 2 This is a schematic diagram of the mesh pattern of a set of strong seams and a set of weak seams with an inclination angle according to the present invention;

[0036] Figure 3 This is a schematic diagram of the fully fractured orthogonal fractured mesh pattern of the present invention.

[0037] Explanation of reference numerals in the attached figures:

[0038] 1. Strong seam, 2. Weak seam. Detailed Implementation

[0039] The present invention will now be described in detail with reference to the accompanying drawings and embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0040] All embodiments are for a 400*400*400mm true triaxial wellbore stability physical simulation experimental system, and the final large-sized fractured rock samples prepared are all 400*400*400mm in size. However, the rock sample preparation method of the present invention includes, but is not limited to, the above-mentioned size.

[0041] Example 1

[0042] 1) Based on formation imaging logging, downhole rock slugging, downhole core samples, and CT scans of target block A, the fracture density was found to be 7.5 fractures / meter, the average macroscopic fracture width was approximately 0.6 mm, the cementation strength of the fractures was 5 MPa, and the angle between the fractures and the horizontal surface was 0°. Based on the fracture information collected above, it can be seen that the fracture mode of the fractured formation belongs to... Figure 1 The simple layered horizontal fracture network pattern in the model, combined with its fracture density, fracture width, and simulated sample size, is used to calculate the fracture interval of the simulated rock sample. For a 400mm size, a 100mm fracture interval can be set. The specific calculation method is based on the similarity criterion and directly sets it proportionally. Thus, there are 3 fractures in a 400mm sample, i.e., 7.5 fractures / meter * 0.4 meters = 3 fractures. The fracture interval in the simulated sample is 400mm / (3+1) = 100mm. At this time, it can be seen that the size of each simulated rock sample is 400*400*100mm, and the number of simulated rock samples is 4. The fracture width is set to 0.6mm to simulate its fracture characteristics.

[0043] 2) Select complete rock outcrops of the corresponding stratigraphic position and prepare 4 standard-sized cuboid rock blocks with dimensions of 400*400*100mm.

[0044] 3) Place the simulated rock samples in a cubic mold according to the crack width, number, and size determined in the above steps, and according to the corresponding crushing mode. Before placing the simulated rock samples in the mold, the surface of the simulated rock samples can be cleaned. The purpose of cleaning is solely to ensure better bonding between the crack filling material and the rock blocks during later crack pouring, thus improving the bonding performance. Place four water-soluble papers at the four vertices of the contact surfaces of the simulated rock samples, one water-soluble paper at the center point of the contact surface, and another water-soluble paper at each of the four quarter points on the diagonal of the contact surface near the vertices of the contact surface, for a total of nine water-soluble papers. The thickness of the water-soluble paper at each contact corner point is 0.6 mm. By placing water-soluble paper between the contact surfaces of the simulated samples, point contact between the standard rock blocks is ensured through the water-soluble paper to simulate cracks.

[0045] 5) A rock-like material made of water, cement and gypsum was used to pour the simulated rock samples stacked in sequence. The samples were cured at room temperature for 18 days and then demolded to obtain the simulated rock sample of the fractured strata. The simulated sample was then cut into 400*400*400mm pieces.

[0046] In this embodiment, the mass ratio of water, cement, and gypsum is water:cement:gypsum = 1:2:1.5. Under this ratio, the shear strength of the solidified rock material is equal to the cementation strength of the cracks.

[0047] Example 2

[0048] 1) Based on formation imaging logging, downhole rockfall data, downhole core samples, and CT scans of target block B, the following data were collected: Strong fracture group density: 19 fractures / meter; average fracture width: approximately 0.8 mm; angle to the horizontal plane: 45°; Weak fracture group density: 9 fractures / meter; fracture width: 0.6 mm; angle to the horizontal plane: 135°. The imaging logging interpretation results directly provide the dip angle ranges for both strong and weak fractures. Furthermore, core and rockfall observations also directly reveal the dip angle of the fractures to the horizontal plane. The cementation strength of the fractures is 5 MPa. Based on the fracture information collected above, it can be seen that the fracture mode of the fractured formation belongs to... Figure 2 The mesh pattern in the middle has one set of strong seams and one set of weak seams with an angle. Figure 2 In this context, 1 refers to a strong seam and 2 refers to a weak seam.

[0049] Combining the crack density, crack width, and simulated sample size, the crack spacing of the simulated rock sample was calculated. Based on the similarity criterion, it was calculated that for a 400mm size, the spacing between strong crack groups should be 50mm, and the spacing between weak crack groups should be 100mm. (Calculation method: The diagonal length of a 400mm*400mm square cross-section is 400*1.414=565.5, rounded to 566mm. The number of strong cracks within the diagonal length should be: 566*19 / 1000=10.75. Strong crack group spacing = 566 / (10.75+1)=4) 8.17, rounded to 50mm, the number of weak cracks within the diagonal length should be: 566*9 / 1000=5.09, weak crack group interval=566 / (5.09+1)=92.9, rounded to 100mm). At this time, it can be seen that the size of each simulated rock sample is 400*100*50mm. In this example, it is first stacked horizontally according to the size of (400*1.414)*((400*1.414))*400, and then rotated at a certain angle (45 degrees) to cut out a 400*400*400 cube. Since each piece measures 100*50*400, a total of the following dimensions are required: Length: (400*1.414 / 100) = 5.65, rounded to 6; Height: (400*1.414 / 50) = 11.312, rounded to 12. Therefore, a total of 6*12 = 72 rock samples are needed to simulate their fracture characteristics.

[0050] 2) Select complete rock outcrops of the corresponding strata and prepare 72 standard-sized simulated rock samples with a size of 400*100*50mm in the shape of cuboids.

[0051] 3) Remove the ash from the surface of the prepared simulated rock sample.

[0052] 4) Place the simulated rock samples in a cubic mold according to the crack width, number, and size determined in the above steps, and according to the corresponding fracture pattern. Place 5 pieces of water-soluble paper between the contact surfaces of the simulated rock samples. The thickness of the water-soluble paper at each contact corner of the strong fracture group is 0.8 mm, and the thickness of the water-soluble paper at each contact corner of the weak fracture group is 0.6 mm. Place 4 pieces of water-soluble paper at the 4 vertices between the contact surfaces of the simulated rock samples, and 1 piece of water-soluble paper at the center point of the contact surface. It should be noted that during mold making, for ease of placement, the simulated rock samples representing the strong and weak surfaces can be placed horizontally first. After casting and curing, the samples can be cut by rotating them at a specific angle to prepare the second type of pattern sample.

[0053] 5) The simulated rock sample was cast by mixing the prepared cement and gypsum and stacking them in sequence. It was cured at room temperature for 21 days and demolded to obtain the simulated rock sample of the fractured strata. The simulated sample was cut into 400*400*400mm size.

[0054] In this embodiment, the mass ratio of water, cement, and gypsum is water:cement:gypsum = 1:2:1.5. Under this ratio, the shear strength of the solidified rock material is equal to the cementation strength of the cracks.

[0055] Example 3

[0056] 1) Based on formation imaging logging, downhole rockfall data, downhole core samples, and CT scans of target block C, fractures were collected, including transverse and vertical fractures. The angle between the transverse fractures and the horizontal surface was 0°, and the angle between the vertical fractures and the horizontal surface was 90°. The fracture width was 1 mm, and the cementation strength of the fractures was 5 MPa. Based on the fracture information collected above, it can be seen that the fracture mode of the fractured formation belongs to... Figure 3 The fully fractured orthogonal fracture network pattern in the model is used, combined with its fracture density, fracture width, and simulated sample size to calculate the fracture interval of the simulated rock sample. In this example, the calculated fracture interval is 50 mm. The calculation method is as follows: fracture group density is 18 fractures / meter. Under a size of 400 mm, the number of transverse fractures is 400*18 / 1000 = 7.2. The fracture group interval is 400 / (7.2+1) = 48.78, which is rounded to 50 mm. Similarly, the vertical fracture interval is calculated as 400 / (7.2+1) = 48.78, which is rounded to 50 mm. The corresponding simulated rock sample size is 50*50*50 mm, and the number is (400 / 50)*(400 / 50)*(400 / 50) = 512 pieces. The average macroscopic fracture width is about 1 mm, simulating its fracture characteristics.

[0057] 2) Select complete rock outcrops of the corresponding strata and prepare 512 standard-sized cuboid rock blocks with dimensions of 50*50*50mm.

[0058] 3) Remove the ash from the surface of the prepared simulated rock sample.

[0059] 4) Place the simulated rock samples in a cubic mold according to the crack width, number, and size determined in the above steps, and according to the corresponding crushing mode. Place 9 pieces of water-soluble paper between the contact surfaces of the simulated rock samples, 4 pieces of water-soluble paper at the 4 vertices of the contact surfaces, 1 piece of water-soluble paper at the center point of the contact surface, and 1 more piece of water-soluble paper at each of the four quarter points on the diagonal of the contact surface of the simulated rock samples, close to the vertices of the contact surface. The thickness of the water-soluble paper at each contact corner point is 1 mm.

[0060] 5) The simulated rock sample was cast by mixing the prepared cement and gypsum and stacking them in sequence. It was cured at room temperature for 23 days and demolded to obtain the simulated rock sample of the fractured strata. The simulated sample was cut into 400*400*400mm size.

[0061] In this embodiment, the mass ratio of water, cement, and gypsum is water:cement:gypsum = 1:2:1.5. Under this ratio, the shear strength of the solidified rock material is equal to the cementation strength of the cracks.

[0062] The simulated specimen of this invention includes simulated rock samples and rock-like materials. The simulated rock samples are placed in a simulated specimen mold according to a corresponding stacking method. Water-soluble paper is placed between the contact surfaces of the simulated specimens to ensure point contact between the standard rock blocks through the water-soluble paper, thus simulating cracks. This invention does not employ the existing method of completely filling the simulated cracks with water-soluble paper; instead, it uses only a smaller amount of water-soluble paper to simulate cracks. Because the water-soluble paper does not completely occupy the gaps between the simulated rock samples, the rock-like material can penetrate the gaps more completely, creating cracks with cemented strength. The better the rock-like material fills and the better the cementation, the better the simulation effect.

[0063] As can be seen, this invention proposes a method for preparing simulated samples for fractured formations, as well as the prepared simulated samples. This invention utilizes data from formation imaging logging, downhole rock fragmentation, downhole core analysis, and CT scans to fully collect and quantify the distribution characteristics of formation rock fractures; and, following a proportional principle, sets up simulated samples corresponding to the distribution morphology, width, number density, and cementation strength of the fractures. This achieves precise control over the number density, width, distribution morphology, and cementation strength of large-scale model rock samples from fractured formations, providing a basic sample for conducting physical simulation experiments on the stability of large wellbore walls in fractured formations, and providing necessary assurance for studying their deformation laws, instability characteristics, and mechanisms.

[0064] The fractured strata rock samples of the present invention contain both cemented through fractures and cemented non-through fracture structures.

[0065] A through fracture is a crack that extends from the interior of the rock to the surface of the sample. Most traditional cutting methods result in through fractures. A non-through fracture, on the other hand, is a crack that extends only inside the rock sample and does not reach the outer surface.

[0066] The 400mm specimens described in this article all have through-cracks. If a layer of cement is wrapped around the outside, non-through-cracks can be prepared.

Claims

1. A method for preparing a simulated rock sample from fractured strata, characterized in that, The method includes the following steps: (1) Collect fracture information of the rocks in the strata to be simulated, determine the fracture mode, and quantify the fracture distribution characteristics; The rock formation to be simulated is a fractured rock formation; (2) Determine the standard size and quantity of the simulated rock samples based on the fracture mode, crack distribution characteristics and simulated sample size of the rocks in the strata to be simulated; The simulated rock sample is a cube prepared from a natural outcrop of the rock in the strata to be simulated; (3) The simulated rock samples are stacked in the simulated sample mold according to the fracture mode, and water-soluble paper is placed between the contact surfaces of the simulated rock samples; the thickness of the water-soluble paper is equivalent to the width of the crack; the water-soluble paper contact points between the contact surfaces of the simulated rock samples are at least five; and the water-soluble paper contact points are at least distributed on the four vertices of the contact surface of the simulated rock samples and the center point of the contact surface. (4) The simulated rock sample placed in the simulated sample mold is cast and molded using a rock-like material, cured, and demolded to obtain the simulated rock sample of the fractured strata.

2. The method for preparing simulated rock samples from fractured strata according to claim 1, characterized in that, In step (1), the fracture information of the rock formation to be simulated is obtained through formation imaging logging, downhole rock slugging, downhole core and CT scan.

3. The method for preparing simulated rock samples from fractured strata according to claim 1, characterized in that, In step (1), the crack distribution characteristics include the crack distribution morphology, width, number density and bonding strength.

4. The method for preparing simulated rock samples from fractured strata according to claim 1, characterized in that, In step (1), the breaking mode includes a simple layered horizontal seam pattern, a set of strong seams and a set of weak seams with an inclination angle, or a completely breaking orthogonal breaking seam pattern.

5. The method for preparing simulated rock samples from fractured strata according to claim 1, characterized in that, In step (2), the size of the simulated sample is 300*300*300mm, 400*400*400mm or 1000*1000*1000mm.

6. The method for preparing simulated rock samples from fractured strata according to claim 1, characterized in that, In step (3), the simulated rock sample is placed in front of the simulated sample mold, and the surface of the simulated rock sample is de-dusted.

7. The method for preparing simulated rock samples of fractured strata according to claim 1, characterized in that, Nine water-soluble paper contact points are set between the contact surfaces of the simulated rock sample. The water-soluble paper contact points are also distributed on four equal-division points on the diagonal of the contact surface of the simulated rock sample, close to the vertex of the contact surface.

8. The method for preparing simulated rock samples of fractured strata according to claim 1, characterized in that, In step (4), the rock-like material is prepared from water, cement and gypsum; the shear strength of the solidified rock-like material is equal to the cementation strength of the crack.

9. A simulated rock specimen of fractured strata prepared by the method for preparing simulated rock specimens of fractured strata according to any one of claims 1-8.

Citation Information

Patent Citations

  • Preparation method of irregular easily-broken coal rock block test piece

    CN102866050A

  • Three-dimensional intermittent cut-through crack production apparatus and method of cuboid rock test sample

    CN106092699A

  • Producing method of intermittent non-filling fracture rock sample model

    CN104833554A

  • A preparing and loading method of a broken rock test sample

    CN105352786A